2016
DOI: 10.1002/2016gc006605
|View full text |Cite
|
Sign up to set email alerts
|

Compositional layering within the large low shear‐wave velocity provinces in the lower mantle

Abstract: The large low shear‐wave velocity provinces (LLSVP) are thermochemical anomalies in the deep Earth's mantle, thousands of km wide and ∼1800 km high. This study explores the hypothesis that the LLSVPs are compositionally subdivided into two domains: a primordial bottom domain near the core‐mantle boundary and a basaltic shallow domain that extends from 1100 to 2300 km depth. This hypothesis reconciles published observations in that it predicts that the two domains have different physical properties (bulk‐sound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 138 publications
(251 reference statements)
5
72
1
Order By: Relevance
“…However, this explanation is not consistent with the observation that many of the non-EM plumes-including Canary and Iceland-are interpreted to be thermochemical plumes due to the apparent width of their conduits in seismic studies (e.g., French & Romanowicz, 2015) and are therefore likely to have entrained chemically heterogeneous material from the base of the mantle. If oceanic hot spots without EM (all lavas have 143 Nd/ 144 Nd > 0.512630) and with EM (at least one lava has 143 Nd/ 144 Nd ≤ 0.512630) signatures are sourced by the LLSVPs, an important conclusion is that the LLSVPs are isotopically heterogeneous, a conclusion supported by recent geodynamic models (Ballmer et al, 2016;Li et al, 2014). While we cannot rule out a shallow contribution to hot spot geochemistry due to uppermost mantle heterogeneities in the melting region of the plume, a range of observations are consistent with a deep origin (e.g., Castillo, 1988;Jackson et al, 2018), and we consider that the geographic association of EM hot spots and LLSVPs is compelling and likely not coincidence.…”
Section: All Em Oceanic Hotspots Are Geographically Associated With Tmentioning
confidence: 83%
See 2 more Smart Citations
“…However, this explanation is not consistent with the observation that many of the non-EM plumes-including Canary and Iceland-are interpreted to be thermochemical plumes due to the apparent width of their conduits in seismic studies (e.g., French & Romanowicz, 2015) and are therefore likely to have entrained chemically heterogeneous material from the base of the mantle. If oceanic hot spots without EM (all lavas have 143 Nd/ 144 Nd > 0.512630) and with EM (at least one lava has 143 Nd/ 144 Nd ≤ 0.512630) signatures are sourced by the LLSVPs, an important conclusion is that the LLSVPs are isotopically heterogeneous, a conclusion supported by recent geodynamic models (Ballmer et al, 2016;Li et al, 2014). While we cannot rule out a shallow contribution to hot spot geochemistry due to uppermost mantle heterogeneities in the melting region of the plume, a range of observations are consistent with a deep origin (e.g., Castillo, 1988;Jackson et al, 2018), and we consider that the geographic association of EM hot spots and LLSVPs is compelling and likely not coincidence.…”
Section: All Em Oceanic Hotspots Are Geographically Associated With Tmentioning
confidence: 83%
“…This is because some Southern Hemisphere oceanic hot spots sample only non-EM compositions. However, we cannot exclude stratified compositional layering within the LLSVPs as a means of separating different deep mantle domains (e.g., EM vs non-EM) sourced by hot spots (Ballmer et al, 2016), but the EM material in this model would need to exhibit a latitudinal stratification to be consistent with the higher concentration of extreme EM hot spots in the Southern Hemisphere. In this way, some Southern Hemisphere plumes entrain plums of EM material, while other Southern Hemisphere plumes entrain only the non-EM LLSVP matrix, giving rise to both austral EM oceanic hot spots (i.e., hot spots that have at least one lava with 143 Nd/ 144 Nd ≤ 0.512630) and austral non-EM oceanic hot spots (i.e., hot spots that do not host any lavas with 143 Nd/ 144 Nd ≤ 0.512630).…”
Section: Distribution Of Em and Himu Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may mark an increase in viscosity (Marquardt & Miyagi, ; Rudolph et al, ), which restricts, without necessarily preventing, flow between the upper and lower mantle. It might also mark a compositional boundary (Ballmer et al, , ). Many of the tomographic images in Figures can be interpreted to be consistent with isolation of the upper and lower mantle from one another, as Wen and Anderson (, ) argued more than 20 years ago.…”
Section: Summary and Possible Implicationsmentioning
confidence: 99%
“…Regarding a possible deeply held prejudice that has slowed understanding, the old‐timers—Francis Birch, Keith Bullen, Norman Haskell, and surely others—might have put the boundary between the upper and lower mantle in the right place, near 1,000 km, and not at 660 km as most have accepted, after that depth seemed to fit with simple images of plate tectonics. Recently, many have suggested that a boundary at 1,000 km is the more important for geodynamics (e.g., Ballmer et al, , ; Čížková & Bina, ; Durand et al, ; Fukao et al, , ; Jenkins et al, ; Marquardt & Miyagi, ; Morra et al, ; Rudolph et al, ; Vinnik et al, ; Wen & Anderson, , ). I argue that a boundary at 1,000 km not only fits seismological data well but also allows greater isolation between the upper and lower mantle than has, until recently, been widely assumed but not total isolation.…”
Section: Introductionmentioning
confidence: 99%